Phototherapy of mycosis fungoides - A. A. Kubanov; A. E. Karamova; L. F. Znamenskaya; A. A. Vorontsova (Онкогематология, 2019)
Currently, phototherapy has been widely used in the treatment of various skin diseases, including mycosis fungoides. The article provides a literature review on the use of various spectra ultraviolet therapy in the treatment of patients with early stages of mycosis fungoides. The mechanisms of action of medium-wave ultraviolet therapy (UVB-311 nm) and PUVA therapy, causing the immunosuppressive, anti-inflammatory and anti-proliferative effect, are described. The results of retrospective studies of PUVA therapy and UVB-311 nm efficacy in patients with cutaneous T-cell lymphoma are presented, as well as modern literature evidence of the need for standardization of phototherapy methods for patients with mycosis fungoides.